A statistical approach for process optimisation of digital light processing 3D printing process. (5th June 2020) - Erdem, Ergin; Sirinterlikci, Arif
This study focuses on experimental design-based approach for process optimisation of a custom-made digital light processing 3D printer. Output measures are developed taking precision and accuracy into consideration. Initial runs were conducted to identify the prominent factors which might play role on output measures. The results indicate that the layer thickness plays a significant role for the two of the developed output measures, photopolymerisation time for one measure, and sequence time for two measures as the interaction-effects also play a role to some. A composite figure that considers all three output measures simultaneously is also developed and a stepwise regression analysis is conducted to identify significant factors. The regression model has moderate R 2 value (68.12%), also indicating that layer thickness and photopolymerisation period play a role. The recommended levels for layer thickness is found to be 0.2 millimetres and photopolymerisation period as 12 seconds based on the composite figure.